A Novel Implementation of an Extended 8x8 Playfair Cipher Using Interweaving on DNA-encoded Data - Safwat Hamad (Institute of Advanced Engineering and Science, 2014)
Recentlty, cryptography makes extensive use of different fields includingbioinformatics. The fundamental idea behind the cipher presented here is to transform any kind of binary message; such as text, sound tracks, and even images, into the form of a single-stranded DNA sequence. Subsequently, digraphs of codon triplets are encrypted using a grid of 8x8 codon matrix that is randomly constructed according to some secret key. Although the encryption/decryption rules were kept almost the same as the classical 5x5 Playfair, using the DNA encoding step makes it almost impossible for an attacker to perform a frequency analysis on that vast number of character digraphs. Furthermore, an interweaving step is added to scramble the encrypted sequence offering more randomness. When compared with other modifications of the Playfair cipher, the proposed method showed a number of advantages including the ability to cipher any type of digital media, the elimination of plain-text preprocessing step, and the applicability to be integrated into larger security systems such as DNA steganography. Furthermore, due to the very weak correlation between cipher-data and original message, the proposed method shows a strong robustness against cipher attacks.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4969